The Last Place You'd Look: True Stories of Missing Persons and the People Who Search for Them - Moore, Carole (Rowman & Littlefield Publishers, 2011)
What happens when a non-custodial parent kidnaps her son? Or a college student vanishes after a night out with friends? Or a middle-aged man seemingly drowns in calm waters? What do family members, friends, and law enforcement do when a beloved goes missing? Here, Moore explores an array of missing persons' scenarios, using real life stories, to uncover the various ways that people go missing, the efforts made to retrieve them, the emotional fallout for family and friends, and the difficulties and challenges such cases present for all involved. She covers parental abductions, intentional disappearances, stranger abductions, the missing and mentally ill, runaways, foul play, and other situations where people go missing. In addition, the criminal justice approach to missing persons is discussed, as Moore looks at the science of missing persons (DNA, forensic dentistry, etc.), resources for family and friends, national organizations such as the National Center for Missing and Exploited Children, and other groups involved in searching and recovering loves ones. Here, readers will discover how people are found, how missing persons' cases are treated, and how and why some stories have happy endings and others do not.